Some Remarks About Pre-School Education in Poland in Comparison with Europe - Kotarba-Kańczugowska, Marta (INSTED: Interdisciplinary Studies in Education & Society, 2011)
The article presents pre-school education in Poland in the context of recent reports of the European Commission (Strategy Europe 2020). It can be seen ? analyzing trends in Europe and their influence on decisions taken at a national level ? that among the aims of the Ministry of Education a high place has been granted to the idea of universalisation of pre-school education. The main area of action is the solution suggested by the Ministry of Education, to create the so-called: other (alternative) forms of preschool education. Is it an effective solution and what will be its fate? The article is an attempt to answer this question.